ANALYSIS ON 113 CASES OF ADVERSE REACTIONS CAUSED BY Β-LACTAM ANTIBIOTICS - Lu, Jianquan; Cai, Chunyue; Gu, Yufeng; Tang, Yanhui; Xue, Jinbiao; Huang, Kaijian (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objectives of this study were to learn about the characteristics and rules of the occurrence of adverse reactions caused by lactam antibiotics and provide a reference for clinical drug use. Methods: A retrospective study was made to analyse the 113 case reports of adverse reactions caused by β-lactam antibiotics collected in our hospital between 2007 and 2009. Results: 113 cases of ADR involved 17 kinds of β-lactam antibiotics, headed by ceftriaxone sodium. The most common manifestation was skin and accessory damage; nervous system and gastrointestinal system damage were also easier to find, and the administration route was mainly intravenous infusion. Conclusion: The clinical application of β-lactam antibiotics should pay attention to adverse reaction monitoring and rational drug use to reduce the incidence of adverse reactions.